1982
DOI: 10.1128/jb.150.1.36-45.1982
|View full text |Cite
|
Sign up to set email alerts
|

Isoelectric focusing and crossed immunoelectrophoresis of heme proteins in the Escherichia coli cytoplasmic membrane

Abstract: Isoelectric focusing (IEF), agarose electrophoresis, and crossed immunoelectrophoresis (CIE) were used to resolve the heme-containing proteins of the Escherichia coli cytoplasmic membrane after solubilization by Triton X-100. Two bands in IEF stained for heme with pI values of 4.7 and 5.3. One of the bands, with an isoelectric point of pH 5.3, was present only when the cells were grown to late log or stationary phase and possessed N,N,N,'N'-tetramethyl-p-phenylene-diamine (TMPD) oxidase activity. The pI 4.7 ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

1982
1982
1986
1986

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…The spectra observed with the extracts from cells grown in the presence of 6-ALA are consistent with those reported by others for stationary E . coli exhibiting peaks at about 520, 560 and 620 nm (Green and Gennis, 1983;Kranz and Gennis, 1982). Although the protein concentrations for the cellular extracts from cells grown without 6-ALA supplementation were about one-fifth of those from cells grown with such supplementation, the spectra give no indication of peaks characteristic of difference spectra (reduced-minus-oxidized) for strains synthesizing cytochromes.…”
Section: Difference Spectramentioning
confidence: 99%
“…The spectra observed with the extracts from cells grown in the presence of 6-ALA are consistent with those reported by others for stationary E . coli exhibiting peaks at about 520, 560 and 620 nm (Green and Gennis, 1983;Kranz and Gennis, 1982). Although the protein concentrations for the cellular extracts from cells grown without 6-ALA supplementation were about one-fifth of those from cells grown with such supplementation, the spectra give no indication of peaks characteristic of difference spectra (reduced-minus-oxidized) for strains synthesizing cytochromes.…”
Section: Difference Spectramentioning
confidence: 99%
“…With Paracoccus dentrificans, Azotobacter vinelandii, and Rhodopseudomonas capsulata, the use of artificial electron donors specific for one branch of multibranched electron transport systems made possible the isolation of cytochrome-deficient mutants (16,25,42). In this report, a similar strategy was used to obtain a mutant of E. coli K-12 missing cytochrome d. This mutant was detected by its failure to oxidize the artificial electron donor N,N,N',N'tetramethyl-p-phenylenediamine (TMPD), lending support to the proposal that TMPD donates electrons primarily to the cytochrome d branch (22). In addition to cytochrome d, cytochromes a1 and probably b558 are missing in the mutant.…”
mentioning
confidence: 70%
“…Mutant isolation. Previous studies suggested that high TMPD oxidase activity in the membranes from E. coli grown under conditions of low aeration is due to the presence of cytochrome d (22). Since intact E. coli cells do not react with TMPD (39), an agar plate test was devised that disrupts cells in situ, thus permitting the reaction of TMPD with the electron transport system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the anti-inner membrane serum and the anti-SDH serum were purified by the procedure described by Kranz and Gennis (29).…”
mentioning
confidence: 99%